The pentathlon of the ancient world - Zarnowski, Frank (Academic & Nonfiction Books anthology., 2013)
The pentathlon, comprising competition in the discus, javelin, long jump, sprint and wrestling, was hailed as the ultimate test of athletic versatility and remained a staple of the ancient Greek Olympic Games, Crown Games and Pan-Hellenic festivals for 1,200 years. Still, there is little scholarly consensus over many major aspects of the event. This detailed exploration of the ancient pentathlon discusses the nature of the spectacle, the method of determining a victor, the five sub-events and the order in which they occurred. It also chronicles the history of the event and its champions, the recognition of ancient pentathletes, and the pentathlon's 18-year modern Olympic history and its influence on its contemporary counterpart: the decathlon. A record book and glossary complete this fresh look at one of the ancient world's most renowned sporting competitions.